Quem são os consumidores sustentáveis? - Ana Carolina Baggio Fabricio; Áurio Leocádio (Ciências Sociais Unisinos)
The understanding of the consumer behavior and the decision-making processes involved in their choices is a theme that has been discussed in great depth in recent decades. The identification of variables that can be attributed to characterize a niche market demands specific studies for each category of goods or services. The approach to sustainable consumption and the understanding of its target audience are still intricate questions. Through a literature review on sustainable consumption issues and cultural capital, this article seeks to demonstrate a possible correlation between the option for sustainable consumption and the level of cultural capital of consumers.